Hard carbon material, preparation method and application thereof, and secondary battery

By mixing halogen-containing polymers with thermoplastic resins and reducing metals, heating and smelting and dehalogenation reactions, high-performance hard carbon materials are prepared, which solves the problem of insufficient utilization of halogen-containing waste polymers and high cost of hard carbon raw materials, and achieves efficient, environmentally friendly, green resource utilization and excellent electrochemical performance.

CN119660711AActive Publication Date: 2025-03-21SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411852918.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

In the prior art, halogen-containing waste polymer materials have not been fully utilized, and the hard carbon raw materials are costly, making it difficult to achieve high added value-added green resource utilization.

Method used

By mixing the halogen-containing polymer with a thermoplastic resin and a reducing metal, heating and dehalogenation reaction is carried out to form a carbon-containing precursor and hard carbon material is prepared by carbonization. This method not only realizes pollution-free treatment and high value-added utilization, but also improves the specific capacity and rate performance of hard carbon materials.

Benefits of technology

The pollution-free treatment and efficient utilization of halogen-containing polymer waste are achieved, the raw material cost of hard carbon production is reduced, and the prepared hard carbon materials show excellent electrochemical properties in battery applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660711A_ABST
    Figure CN119660711A_ABST
Patent Text Reader

Abstract

The invention discloses a hard carbon material, a preparation method and application thereof and a secondary battery. The preparation method comprises the following steps: mixing halogen-containing polymer powder and thermoplastic resin, heating and smelting, and cooling to obtain a mixture; mixing the mixture with a reducing metal, and carrying out heating dehalogenation at 100-400 DEG C for 2-12 hours under the protection of inert gas, so as to obtain a dehalogenation sample; washing, drying and carbonizing the dehalogenated sample to obtain a hard carbon material; the thermoplastic resin is polypropylene and / or polyethylene; when the reducing metal is alkali metal, the molar ratio of halogen atoms in the halogen-containing polymer powder to the reducing metal is 1: (1-3); when the reducing metal is alkaline earth metal, the molar ratio of halogen atoms in the halogen-containing polymer powder to the reducing metal is 1: (0.5-1.5). The preparation method can realize high value-added utilization while realizing pollution-free treatment of the halogen-containing polymer waste, and has the advantages of high efficiency, environmental protection, greenness, energy conservation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to a hard carbon material and a preparation method, application and secondary battery thereof. Background Art

[0002] PVC (polyvinyl chloride) is a plastic material widely used in various fields. It has good chemical stability, corrosion resistance, flame retardancy and good processing performance. However, the production, use and disposal of PVC will cause environmental and health problems. Usually, the landfill of PVC materials will exist in the environment for a long time due to its non-degradable characteristics, causing soil and groundwater pollution. PVC is non-degradable under natural conditions and difficult to recycle. Its waste will produce chlorine-containing organic matter such as dioxins and highly corrosive HCl during incineration due to its high chlorine content, so it is one of the plastics that is most harmful to the environment.

[0003] Traditional PVC recycling strategies such as mechanical recycling, processing and reuse have low economic added value, and the material performance deteriorates during the recycling process, making it difficult to sustain the cost. In order to overcome the shortcomings of traditional recycling strategies and tap into the intrinsic value of plastic waste, it is urgent to develop high-value-added green resource utilization technologies for halogen-containing polymers such as PVC.

[0004] Hard carbon is a carbon material with high graphitization degree, high conductivity and high stability. It is widely used in lithium-ion batteries, supercapacitors, fuel cells and other fields. With the rapid development of new energy fields and electronic information industries, the demand for high-performance hard carbon materials is increasing. Currently, hard carbon precursors include biomass, coal, sugars, etc., and the cost of raw materials is relatively high. Therefore, if waste polymers can be fully utilized as carbon sources, the cost of raw materials for hard carbon production will be greatly reduced. Summary of the invention

[0005] The technical problem solved by the present invention is to overcome the defects of the existing halogen-containing waste polymer materials in the prior art that are not fully utilized and the high cost of hard carbon raw materials, and provide a hard carbon material and its preparation method, application and secondary battery. The preparation method of the present invention realizes pollution-free treatment of halogen-containing polymer waste while realizing high value-added utilization, and has the advantages of high efficiency, environmental protection, greenness, energy saving, etc. The prepared hard carbon material has excellent specific capacity and rate performance when applied to batteries.

[0006] In the process of preparing hard carbon materials, the present invention uses halogen-containing polymers as raw materials, first heats and melts the halogen-containing polymers and thermoplastic resins (polypropylene, polyethylene) to obtain a mixture, and the thermoplastic resin can coat the halogen-containing polymer to prevent the halogen-containing polymer from having a larger pore size after HCl overflows during the subsequent dehalogenation process; the halogen-containing polymer and the reducing metal (alkali metal, alkaline earth metal) in the mixture first undergo a dehalogenation reaction to form a carbon-containing precursor and a salt, thereby removing the halogen in the halogen-containing polymer, and then carbonizing the carbon-containing precursor to prepare a hard carbon material with excellent electrochemical performance. In the process of dehalogenation reaction, the reducing metal catalyzes the dehalogenation reaction of the halogen-containing polymer more completely and fixes the highly polluted halogen atoms, and the reducing metal and the generated salt will penetrate into the partially carbonized polymer as a template or pore-forming agent, so that it can be applied to the high-performance negative electrode of sodium / lithium ion batteries to achieve higher specific capacity and rate performance. The preparation method can realize the pollution-free treatment of halogen-containing polymer waste while realizing high value-added utilization, and has the advantages of high efficiency, environmental protection, greenness, and energy saving.

[0007] The present invention solves the above technical problems through the following technical solutions:

[0008] The present invention provides a method for preparing a hard carbon material, which comprises the following steps:

[0009] The halogen-containing polymer powder and the thermoplastic resin are mixed, heated and melted, and cooled to obtain a mixture; the mixture is then mixed with a reducing metal, and heated at 100-400° C. for dehalogenation for 2-12 hours in an inert gas protection to obtain a dehalogenated sample; the dehalogenated sample is washed, dried, and carbonized to obtain a hard carbon material;

[0010] Wherein, the thermoplastic resin is polypropylene and / or polyethylene, and the mass ratio of the thermoplastic resin to the halogen-containing polymer powder is 2%-10%;

[0011] When the reducing metal is an alkali metal, the molar ratio of the halogen atoms in the halogen-containing polymer powder to the reducing metal is 1:(1-3);

[0012] When the reducing metal is an alkaline earth metal, the molar ratio of the halogen atoms in the halogen-containing polymer powder to the reducing metal is 1:(0.5-1.5).

[0013] In the present invention, the halogen-containing polymer powder is preferably polyvinyl chloride (PVC) and / or polyvinylidene chloride (PVDC). The particle size of the halogen-containing polymer powder may be 0.1-1 μm. The halogen-containing polymer powder may also be a powder obtained by washing and mechanically crushing waste halogen-containing polymer products.

[0014] Wherein, the viscosity K value of the polyvinyl chloride may be 50-80, such as 62-60.

[0015] In the present invention, the melt index of the polypropylene may be 10-40 g / 10 min, such as 35 g / 10 min.

[0016] In the present invention, the melt index of the polyethylene may be 10-40 g / 10 min, for example, 25 g / 10 min.

[0017] In the present invention, the mass ratio of the thermoplastic resin to the halogen-containing polymer powder is preferably 2%-8%, for example 5%.

[0018] In the present invention, the heating and melting is generally carried out in a heating furnace. The heating furnace can be conventional in the art, such as a tubular furnace. The heating and melting is generally carried out under an inert atmosphere (such as argon).

[0019] In the present invention, the heating and melting temperature may be 100-140°C, for example 120°C.

[0020] In the present invention, the heating and smelting time may be 1-4 hours, for example 2 hours.

[0021] In the present invention, the alkali metal element is preferably Na and / or K.

[0022] In the present invention, the alkaline earth metal element is preferably one or more of Mg, Ca and Ba.

[0023] In the present invention, when the reducing metal is an alkali metal, the molar ratio of the halogen atoms in the halogen-containing polymer powder to the reducing metal is preferably 1:(1-2), such as 1:1.1, 1:1.2 or 1:1.3.

[0024] In the present invention, when the primary metal is an alkaline earth metal, the molar ratio of the halogen atoms in the halogen-containing polymer powder to the reducing metal is preferably 1:(0.5-1), for example 1:0.55.

[0025] In the present invention, the temperature of the heating dehalogenation is preferably 200-400°C, such as 250°C.

[0026] In the present invention, the heating dehalogenation time is preferably 2-6 hours, such as 3 hours.

[0027] In the present invention, the heating dehalogenation is generally carried out in a tube furnace.

[0028] In the present invention, the inert gas may be conventional in the art, such as nitrogen or argon.

[0029] In the present invention, the washing operation and conditions may be conventional in the art, for example, washing is performed using a mixed solution of deionized water and anhydrous ethanol; in the mixed solution, the volume ratio of the deionized water to the anhydrous ethanol may be 3:1.

[0030] In the present invention, the drying operation and conditions may be conventional in the art.

[0031] In the present invention, according to the common practice in the art, the carbonization is generally performed in an inert gas atmosphere, such as nitrogen or argon.

[0032] In the present invention, the carbonization temperature is preferably 600-1000°C, such as 800°C, 850°C or 900°C.

[0033] In the present invention, the carbonization time may be 0.5 to 10 hours, preferably 3 to 6 hours, for example 4 hours.

[0034] The present invention also provides a hard carbon material prepared by the above-mentioned preparation method.

[0035] In the present invention, the specific surface area of ​​the hard carbon material is preferably 6-10 m 2 g -1 .

[0036] In the present invention, the hard carbon material preferably has a sodium storage capacity greater than 250 mAh / g at a high rate of 20C.

[0037] In the present invention, the hard carbon material preferably has a lithium storage capacity greater than 300 mAh / g at a high rate of 20C.

[0038] The present invention also provides a use of the hard carbon material as mentioned above in a secondary battery.

[0039] The present invention also provides a secondary battery, which comprises the hard carbon material as described above.

[0040] In the present invention, the secondary battery is preferably a lithium ion battery or a sodium ion battery.

[0041] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0042] The reagents and raw materials used in the present invention are commercially available.

[0043] The positive and progressive effects of the present invention are:

[0044] The preparation method of the present invention does not rely on organic solvents to dissolve polymer materials, and can directly achieve a more efficient dechlorination reaction through a simple solid-phase method, thereby promoting graphitization while avoiding chlorine emissions. In addition, the template and pore-forming effects of metals and salts help to increase the specific surface area of ​​the material. The prepared hard carbon material has better electrochemical properties as a lithium / sodium ion battery, especially better specific capacity and 20C rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a scanning electron microscope image of the hard carbon material prepared in Example 1. DETAILED DESCRIPTION

[0046] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0047] The raw material information used in the following examples and comparative examples is shown in Table 1:

[0048] Table 1

[0049]

[0050] Example 1

[0051] (1) 1 g of PVC and 0.05 g of polyethylene were mixed and heated in a tube furnace (under argon atmosphere) for melting at a temperature of 120° C. for 2 h. After cooling, substance A was obtained.

[0052] (2) Substance A and metallic sodium are mixed evenly in a crucible according to the molar ratio of chlorine atoms to metallic sodium in the raw material PVC of 1:1.3, and then added to a tube furnace. In a high-purity argon atmosphere, the mixture is heated to 250°C at a heating rate of 3°C / min, maintained for 3 hours, and then cooled to room temperature to obtain a dehalogenated sample;

[0053] (3) The dehalogenated sample was washed three times with a mixed liquid of deionized water and anhydrous ethanol in a volume ratio of 3:1, and dried to obtain a hard carbon precursor. The hard carbon precursor was then carbonized in a high-purity argon gas using a tubular furnace at a temperature of 5°C / min to 800°C and maintained for 4 hours, and then cooled to obtain a hard carbon negative electrode material.

[0054] Example 2

[0055] Compared with Example 1, except that the polyvinyl chloride powder is replaced by PVDC powder (Dow SARAN 516, extrusion type), the other parameters and conditions are the same as those in Example 1.

[0056] Example 3

[0057] Compared with Example 1, except that metallic sodium is replaced by metallic potassium, the other parameters and conditions are the same as those of Example 1.

[0058] Example 4

[0059] Compared with Example 1, except that metallic sodium is replaced by metallic potassium and the molar ratio of chlorine atoms and metallic potassium in PVC is adjusted to 1:1.1, other parameters and conditions are the same as those in Example 1.

[0060] Example 5

[0061] Compared with Example 1, except that metallic sodium is replaced by metallic magnesium and the molar ratio of chlorine atoms to metallic magnesium in PVC is adjusted to 1:0.55, other parameters and conditions are the same as those in Example 1.

[0062] Example 6

[0063] Compared with Example 1, except that metallic sodium is replaced by metallic calcium and the molar ratio of chlorine atoms to metallic calcium in PVC is adjusted to 1:0.55, other parameters and conditions are the same as those in Example 1.

[0064] Example 7

[0065] Compared with Example 1, except that the carbonization temperature in step (3) is adjusted to 900° C., the other parameters and conditions are the same as those in Example 1.

[0066] Example 8

[0067] Compared with Example 1, except that polyethylene is replaced by polypropylene, other parameters and conditions are the same as those of Example 1.

[0068] Comparative Example 1

[0069] Compared with Example 1, except that metallic sodium is not added in step (1), the other parameters and conditions are the same as those in Example 1.

[0070] Effect Example

[0071] (1) SEM and specific surface area test

[0072] Figure 1 This is a scanning electron microscope image of the hard carbon material prepared in Example 1.

[0073] The specific surface area of ​​the prepared hard carbon material was tested using Anton Paar's specific surface area and pore size analyzer NOVATouch. The test results are shown in Table 1.

[0074] (2) Electrochemical performance test

[0075] Preparation of negative electrode: The hard carbon materials prepared in Examples 1 to 8 and Comparative Example 1 were subjected to half-cell tests respectively. The test method was as follows: the hard carbon material, superconductive carbon black (Super P) and PVDF were configured in a mass ratio of 8:1:1, mixed evenly using a homogenizer, and then coated on a copper foil current collector, and dried overnight in a vacuum oven at 90°C. Subsequently, the obtained electrode was cut into a disc-shaped battery electrode with a diameter of 12 mm for standby use, with an average mass load of ≈2 mg cm -2 .

[0076] The assembly of button cells was carried out in an argon-filled glove box. Lithium-ion batteries used lithium metal sheets as counter electrodes and polypropylene monolayers as battery separators. The electrolyte was a 1M LiClO4 mixed solution of ethylene carbonate / diethyl carbonate (EC / DEC, volume ratio 1:1) with 10wt.% fluoroethylene carbonate (FEC) additive added. The wt.% refers to the mass percentage of FEC in the electrolyte. The charge and discharge tests were carried out on a LAND CT2001A battery tester in the potential range of 0.001-3.0V.

[0077] The sodium ion battery uses a sodium metal sheet as the counter electrode, a glass fiber monolayer as the battery separator, and a nickel foam disc as the auxiliary. The electrolyte is a 1M NaPF6 diethylene glycol dimethyl ether solution. After assembly, it is left to age for 8 hours. Constant current charge / discharge tests are performed on the LAND CT2001A battery test system, with a voltage range of 0.001 to 3.0V vs. Li / Li + .

[0078] The test results are shown in Table 2:

[0079] Table 2

[0080]

[0081] According to the above experimental results, it can be seen that the hard carbon negative electrode material prepared by the present invention has excellent electrochemical properties, especially specific capacity and rate performance.

[0082] In Comparative Example 1, due to the lack of metal catalysis during the preparation process, the dehalogenation reaction is less efficient at the same temperature, which is not conducive to the formation of highly conductive carbon. In addition, due to the lack of the template effect of metal and salt, the prepared hard carbon material has a small specific surface area and a low specific capacity.

[0083] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon material, characterized in that: It includes the following steps: The halogen-containing polymer powder and the thermoplastic resin are mixed, heated and melted, and cooled to obtain a mixture; the mixture is then mixed with a reducing metal, and heated at 100-400° C. for dehalogenation for 2-12 hours in an inert gas protection to obtain a dehalogenated sample; the dehalogenated sample is washed, dried, and carbonized to obtain a hard carbon material; Wherein, the thermoplastic resin is polypropylene and / or polyethylene, and the mass ratio of the thermoplastic resin to the halogen-containing polymer powder is 2%-10%; When the reducing metal is an alkali metal, the molar ratio of the halogen atoms in the halogen-containing polymer powder to the reducing metal is 1:(1-3); When the reducing metal is an alkaline earth metal, the molar ratio of the halogen atoms in the halogen-containing polymer powder to the reducing metal is 1:(0.5-1.5).

2. The method for preparing a hard carbon material according to claim 1, characterized in that: The halogen-containing polymer powder is polyvinyl chloride (PVC) and / or polyvinylidene chloride (PVDC); The viscosity K value of the polyvinyl chloride is preferably 50-80, such as 62-60; And / or, the particle size of the halogen-containing polymer powder is 0.1-1 μm.

3. The method for preparing a hard carbon material according to claim 1, characterized in that: The alkali metal element is Na and / or K; And / or, the alkaline earth metal element is one or more of Mg, Ca and Ba.

4. The method for preparing a hard carbon material according to claim 1, characterized in that: When the reducing metal is an alkali metal, the molar ratio of the halogen atoms in the halogen-containing polymer powder to the reducing metal is 1:(1-2), for example, 1:1.1, 1:1.2 or 1:1.3; And / or, when the primary metal is an alkaline earth metal, the molar ratio of the halogen atoms in the halogen-containing polymer powder to the reducing metal is 1:(0.5-1), for example, 1:0.

55.

5. The method for preparing a hard carbon material according to claim 1, characterized in that: The melt index of the polypropylene is 10-40 g / 10 min, for example 35 g / 10 min; And / or, the polyethylene has a melt index of 10-40 g / 10 min, such as 25 g / 10 min; And / or, the mass ratio of the thermoplastic resin to the halogen-containing polymer powder is 2%-8%, for example, 5%.

6. The method for preparing a hard carbon material according to claim 1, characterized in that: The heating and melting temperature is 100-140°C, for example 120°C; And / or, the heating and smelting time is 1-4 hours, for example 2 hours.

7. The method for preparing a hard carbon material according to claim 1, characterized in that: The temperature of the heating dehalogenation is 200-400°C, for example 250°C; And / or, the heating dehalogenation time is 2-6 hours, for example 3 hours; and / or, the carbonization temperature is 600-1000° C., such as 800° C., 850° C. or 900° C.; And / or, the carbonization time is 0.5 to 10 hours, preferably 3 to 6 hours, for example 4 hours.

8. A hard carbon material, characterized in that: The hard carbon material is prepared according to the method for preparing the hard carbon material according to any one of claims 1 to 7.

9. Use of the hard carbon material according to claim 8 in a secondary battery.

10. A secondary battery, characterized in that: It comprises the hard carbon material as claimed in claim 8.

Citation Information

Patent Citations

  • Thermoplastic resin composition

    CA2013829A1

  • Nonaqueous electrolyte solution for batteries, novel compound, polymer electrolyte, and lithium secondary battery

    CN105103361A

  • Method for preparing hard carbon from polyvinyl chloride waste, coal tar and fractions thereof and application

    CN116281949A

  • Polyvinyl chloride derived hard carbon material, preparation method and application thereof, and battery

    CN118306978A

  • Hard carbon material, preparation method and application thereof, and battery

    CN118448630A

Cited By

  • Hard carbon material and preparation method therefor and use thereof, and battery

    WO2025228048A1